Come what may: by Gustaf A. Sword - Sword, Gustaf A.
"Caleb teams up with Rachel to lead Patrick Henry College to the National Moot Court Championship. Along the way, he is caught in a moral tug-of-war between his parents-- a newly Christian father, and a constitutional attorney mother. As the PHC moot court team and the U.S. Supreme Court simultaneously grapple with legal cases involving abortion, Caleb clashes with his mother and his own conscience as he struggles to internalize his beliefs and stand on Biblical values"--Videodisc container.